Oxidation of HDAC4 by Nox4-derived H2O2 maintains tube formation by endothelial cells - Schader, Tim; Löwe, Oliver; Reschke, Christina; Malacarne, Pedro; Hahner, Fabian; Müller, Niklas; Gajos-Draus, Anna; Backs, Johannes; Schröder, Katrin (Redox Biology, 2020)
NADPH oxidases produce reactive oxygen species that differ in localization, type and concentration. Within the Nox family only Nox4 produces H2O2 which can directly oxidize cysteine residues. With this post-translational modification, activity, stability, localization and protein-protein interactions of the affected protein is altered. Nox4 controls differentiation, cellular homeostasis and prevents inflammation. Therefore, is likely that epigenetic mechanisms contribute to the effects of Nox4. One group of epigenetic modifiers are class IIa histone deacetylases (HDACs). We hypothesize that Nox4-derived H2O2 oxidizes HDACs and analyzed whether HDACs can be differentially oxidized by Nox4. As an artificial system, we utilized HEK293 cells, overexpressing Nox4 in a tetracycline-inducible manner. HDAC4 was oxidized upon Nox4 overexpression. Additionally, Nox4 overexpression increased HDAC4 phosphorylation on Ser632. H2O2 disrupted HDAC4/Mef2A complex, which de-represses Mef2A. In endothelial cells such as HUVECs and HMECs, overexpression of HDAC4 significantly reduced tube formation. Overexpression of a redox insensitive HDAC4 had no effect on endothelial tube formation. Treatment with H2O2, induction of Nox4 expression by treatment of the cells with TGFβ and co-overexpression of Nox4 not only induced phosphorylation of HDAC4, but also restored the repressive effect of HDAC4 for tube formation, while overexpression of a redox dead mutant of Nox4 did not. Taken together, Nox4 oxidizes HDAC4, increases its phosphorylation, and eventually ensures proper tube formation by endothelial cells.
Im Text ist die "2" tiefgestellt
Gesehen am 14.10.2020